Analysis Using Temperature Sensor DS18B20 Hydroponic Plants Smart In Vertical Agriculture - Rasid M; Marzuki Marzuki (Bandar Lampung University (UBL), 2017)
The technology is now highly developed rapidly. One example of progress is the human automation system tools. A wide variety of tools have been created with the aim to facilitate human in doing hisjob, but with the automation system is then expected human tools that already exist can now work more efficiently and effectively lighten the burden of the work of man. Agriculture now also beenhighly developed. It can be seen from the limited agricultural land so that people start looking formore efficient ways of doing agricultural development with the limited land owned. This developmentcan be seen with the new agricultural methods, one of which is known as hydroponic energy system.The automation system can be applied in farming methods with the making automation tool that cancontrol some aspects such as water temperature, acidity / alkalinity of the water (pH) and nutrients in plants using hydroponic plant maintenance. By incorporating technology into the right farmingmethods, then we will get results more effective and efficient and will directly alleviate the burden of the work of man. On the basis of this thought behind the making of the automation system for thecontrol of this hydroponic plants. Hydroponics is growing plants and growing techniques that utilize water instead of soil by emphasizing the need nutrients, temperature and pH for plants. Needs ofhydroponic water at less than the plant with soil media, so is suitable for areas that have water supply and limited land